(untitled) (Scientific journal of the Fergana State University, 2025)
The article considers the relationship between the productivity elements of the Navruz and Atoi-85 wheat varieties at different seeding rates (100, 200 and 300 pcs/m2) and the use of mineral nitrogen at the rate of 200 kg/ha in the form of urea. It was revealed that the hydrothermal coefficient of the Gissar Valley of Tajikistan over the years of research (2008-2012) is at the level of GTC 0.26, which indicates an insufficient level of moisture in the territory. It was found that with an increase in the seeding rate, a significant change in the length of the productive straw, the length and weight of the ear is observed. When using mineral nitrogen, the ear weight of the Navruz variety increases from 1.64 to 3.4 g, and of the Atoi-85 variety from 2.0 to 3.25 g. Under the influence of environmental conditions, the number of stem nodes and their lengths change significantly.